Assessing knowledge anxiety in researchers: a comprehensive measurement scale - Yu Zhenlei; Lin Song; Dong Minyi; He Qiang (PeerJ)
Background The rapid pace of knowledge production has introduced a phenomenon termed “knowledge anxiety”, a psychological state where researchers feel inadequate in keeping up with emerging information. This state can negatively affect productivity and mental well-being, yet there is no comprehensive tool to measure knowledge anxiety across different research domains. Methods We employed a mixed-methods approach to develop a multidimensional scale for assessing knowledge anxiety. Initial items were generated through a literature review and qualitative interviews with 313 researchers. After pilot testing, the main study involved 26 participants. The scale was refined through exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) to ensure its structural validity and reliability. Results EFA resulted in a 16-item scale with four distinct factors: cognitive, emotional, behavioral, and capability-related anxieties. CFA confirmed a strong model fit, with standardized factor loadings between 0.549 and 0.887. The scale demonstrated high reliability, with a composite Cronbach’s alpha of 0.883. Conclusions This newly developed scale offers a reliable and valid measure of knowledge anxiety, providing researchers with a valuable tool to assess the psychological impacts of knowledge overload.